The Effect of Working Capital Management on Profitability and Business Risk in Indonesian Manufacturing Companies - Rahmat Setiawan; Artha Merika Indah Puspita Sari (Ekonomi Bisnis, 2021)
Company policies related to working capital are very important to note, given the amount of working capital as a proportion of company assets. The financial manager must be able to maximize the use of working capital for the benefit of shareholders. This research aims to assess and analyze the effect of working capital management measured by the cash conversion cycle on profitability and risk in manufacturing companies in Indonesia.  Data used are from financial statements of manufacturing companies listed on the Indonesia Stock Exchange and fulfill research requirements using with purposive sampling method amount to 81 companies from 2014 to 2018. The result of the study shows that the cash conversion cycle has a negative significant effect on the profitability and risk of the company.